Determinants on the adoption of Takaful among secondary school teachers in Malaysia (a case study in Kedah) - Zakaria, Aliya Syaffa; Muhammad Ammar Shafi, Muhammad Ammar Shafi; Mohd Razali, Siti Noor Asyikin; Yusoff, Mohd Zarir; Kamaruddin, Nor Kamariah (2024)
Malaysia's Takaful industry is the second largest outside the Arab region. Takaful is one of Malaysia's Islamic finance industry sectors. Takaful has experienced remarkable growth since its inception in the 1980s. However, penetration of Takaful among Malaysian consumers remains modest despite the industry's expansion. Several previous studies have examined the extent of Takaful penetration among public sector employees. Thus, the purpose of the present study is to investigate the adoption of Takaful, with a focus on secondary school teachers as respondents. This paper aims to investigate the factors influencing the adoption of Takaful among secondary school teachers in Sungai Petani, Kedah. The focus of the study will be on a number of determinants of Takaful adoption, including word-of-mouth (WOM) promotion, awareness and knowledge of Takaful, the roles of mass media, and the performance of Takaful operators. Stratified sampling will be utilized to acquire respondents progressively. This study collected primary data from 120 secondary school teachers in Sungai Petani, Kedah, via questionnaires that were distributed to them. The data were analyzed by multiple linear regression method using SPSS 23.0. This study's findings point out that all hypotheses were substantiated. Furthermore, promotion by word-of-mouth and the roles of mass media have the greatest impact on the level of Takaful adoption among secondary school teachers.